1999
DOI: 10.1088/0953-8984/11/2/012
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of ferrimagnets on chains and square lattices

Abstract: A linear spin wave analysis of dimerization of alternating Heisenberg system with spins s 1 and s 2 on linear chain as well as square lattice is presented. Among the several possible dimerized configurations considered in two dimensions the plaquette configuration is found to be energetically the most favored one. Inclusion of a variable nearest neighbor exchange coupling J(a) = J a leads to a uniform power law behavior: that is to say, the same δ-dependence is found (i) in chains as well as in square lattices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…This decrease is faster for higher  , and scales with T as . At the critical value of frustration, 2 T , c  the free energy become imaginary and our LSW theory fails to go beyond this value of frustration. It was reported earlier [2,20] that at T = 0.0 the ground states energy increases with frustration parameter and then starts to decrease for values of frustration close to c  .…”
Section: Frustrated Ferrimagnetic Chain With δ =mentioning
confidence: 92%
See 4 more Smart Citations
“…This decrease is faster for higher  , and scales with T as . At the critical value of frustration, 2 T , c  the free energy become imaginary and our LSW theory fails to go beyond this value of frustration. It was reported earlier [2,20] that at T = 0.0 the ground states energy increases with frustration parameter and then starts to decrease for values of frustration close to c  .…”
Section: Frustrated Ferrimagnetic Chain With δ =mentioning
confidence: 92%
“…At T = 0 it shows the ground state energy of the system. It was founded that dimerization at T = 0 reduces ground state energy [2,14], it does the same with free energy. We found that the decrease of the free energy goes as .…”
Section: Using Expanded Formmentioning
confidence: 98%
See 3 more Smart Citations